Penerapan Metode Maut Dalam Pemilihan Wartawan Terbaik Dengan Pembobotan Entropy (Kasus Koran Radar Group) - Sari, Cindy Nanda; Mesran, M; Sihite, A. M Hatuaon (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2023)
The online press media Radar is an online media entity of Radarindo that is signed by the editor-in-chief. The high number of journalists in the Koran Radar Group makes it challenging for the editor-in-chief to select the best journalists, as there lacks a suitable system for this purpose, including an effective system within the Koran Radar Group. Without a clear system, ensuring an objective and fair selection of the best journalists becomes difficult. The selection of the best journalists is crucial to guarantee the quality and accuracy of information delivered to the public. Hence, a system has been created to aid in the assessment process for choosing the best journalists for the Koran Radar Group. This system utilizes the MAUT method and Entropy weighting to evaluate the values of each criterion and rank alternative candidates. It is expected that implementing this decision support system will provide a positive contribution to the process of selecting the best journalists for the company.After conducting the ranking process, the results obtained from the application of the MAUT method and Entropy weighting show that alternative (A2) with the name Sehat Sembiring scored 0.00983, making it the best alternative in the selection of the best journalists for the Koran Radar Group.